2016
DOI: 10.3389/fpsyg.2016.00112
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Supervisors’ Big Five Personality Traits and Employees’ Experiences of Abusive Supervision

Abstract: The present study investigates the relation between supervisors’ personality traits and employees’ experiences of supervisory abuse, an area that – to date – remained largely unexplored in previous research. Field data collected from 103 supervisor-subordinate dyads showed that contrary to our expectations supervisors’ agreeableness and neuroticism were not significantly related to abusive supervision, nor were supervisors’ extraversion or openness to experience. Interestingly, however, our findings revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 76 publications
2
38
1
3
Order By: Relevance
“…A conscientious person has traits such as hardworking, persistent, wellorganised, and goal oriented (Camps, Stouten, & Euwema, 2016). The relationship between conscientiousness and ethical predisposition is generally positive (Bratton & Strittmatter, 2013), where conscientiousness was found to link positively with ethical use of internet facility (Karim, Zamzuri, & Nor, 2009) and ethical leadership (Kalshoven et al, 2011).…”
Section: Conscientiousnessmentioning
confidence: 99%
See 3 more Smart Citations
“…A conscientious person has traits such as hardworking, persistent, wellorganised, and goal oriented (Camps, Stouten, & Euwema, 2016). The relationship between conscientiousness and ethical predisposition is generally positive (Bratton & Strittmatter, 2013), where conscientiousness was found to link positively with ethical use of internet facility (Karim, Zamzuri, & Nor, 2009) and ethical leadership (Kalshoven et al, 2011).…”
Section: Conscientiousnessmentioning
confidence: 99%
“…Individuals high on neuroticism tend to experience negative moods such as anxiety, fear, depression, and irritability as well as other physical symptoms. In many studies, neuroticism has been found to be the significant predictor of unethical behaviour (e.g., Camps et al, 2016;Walumbwa & Schaubroeck, 2009). People high in neuroticism are insecure, deprived, angry, frustrated, and moody; thus, are more susceptible to negative emotions.…”
Section: Neuroticism or Emotional Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…While some researchers have reconsidered the distinction between active and passive forms of abusive supervision as suggested by Mitchell and Ambrose (), it is rather surprising that these researchers (e.g. Breevaart & de Vries, ; Camps, Stouten, & Euwema, ) and even Mitchell and Ambrose () did not report the internal consistency of the subscale representing passive acts of abuse. Hence, although the consistency value in our study is rather low, we cannot say whether this is a unique feature of our study or a general problem of the subscale.…”
Section: Discussionmentioning
confidence: 99%